(untitled) (Fisioterapia e Pesquisa, 2015)
The effects of an intervention program with global postural reeducation (GPR) and a period of no treatment (8 weeks) were evaluated by kinematic analysis and evaluation of static and dynamic balance of an adult with Cerebral Palsy (CP). Evaluations of balance were made using the Berg Balance Scale, as well as gait kinematics evaluations, in which spatiotemporal and angular variables were analyzed. These assessments were made at the beginning and at the end of each intervention period. To characterize the parameters examined, descriptive statistics (mean and standard deviation) was used. The studied subject showed improvement of balance after the intervention period and, regarding angular variables, decreased hip extension and less trunk tilt were found. With the improvement of balance, hip extension and alignment of the trunk of the treated patient, it is suggested that the GPR intervention method can be effective as a practice of physical therapy for CP; however, more effective results may be associated with continuous treatment with this method, since during the intervals of the intervention, there was a reduction in balance.